S1RS Composition: An innovative abstract art development for new abstract painters through the analysis of seafarer and renjana with a comprehension of the gestalt principle - Shaari, Zuriati Mohamed; Mohamed Amin , Noor Hidawati; Arzain , Noriza; W. Mohamad Daud , Wan Samiati Andriana; Mohd Ghazali , Fariz Azmir (Journal of Islamic, Social, Economics and Development, 2024)
S1RS has resulted from a practice-based research that concentrates on the epistemology of abstract paintings. Abstract paintings painted by two artists who are presently gaining recognition as prominent figures in the fine art field are the primary focus of the analysis research. The artworks are the outcome of their most recent solo exhibition, which took place in 2023. Balai Seni Melaka was the location of The Seafarer by Rasfan Abu Bakar, while Segaris Gallery in Publika, Kuala Lumpur was the vanue for Renjana by Farif Abdul Jalil. Artists who are beginning to engage with abstract painting have challenges in producing convincing artworks. Indeed, the findings of this study will enable this group of artists to initiate the creation of abstract artworks with a more methodical and structured approach. Wallas Theory, which outlines the four stages of creativity—i) preparation, ii) incubation, iii) illumination, and iv) verification—guides the method of producing this research and painting. This study is based on three fundamental Gestalt Principles: proximity, closure, and symmetry. Using the findings of the study's research, a composition template for abstract paintings called S1RS (Seafarer 1Rumbiya Sagu) has been created. This compositional template was specifically designed for persons who have just begun their engagement in the production of abstract artworks. Additionally, this template has been utilized by the researcher to develop an abstract painting that results in both balanced and visually appealing.